The Perspective of the Youth and Adult Education Student Through Sebastião Salgado's Lens: An Experience Report (Interdisciplinary Studies Journal, 2021)
This article proposes a reflection on Youth and Adult Education (EJA) through the execution of an artistic project carried out in five schools of the Municipality of Fortaleza. The study focuses on the work of photographer Sebastião Salgado, with the aim of developing in EJA students the ability to Create, Enjoy, and Appreciate visual arts, as well as sharpening their critical sense regarding social, political, and economic issues addressed in the studied work. The project proposed reading and enjoying the photographs from the exhibition "Exodus," as well as other works by the photojournalist, focusing on social issues. It provided EJA students with a critical view of the social, political, and economic situation in which they live, while also observing what happens in the world. These issues present a potential rupture of exclusion through art, for students who have been marginalized in socio-economic and educational spheres.
Keywords: Teaching Visual Arts; Youth and Adult Education; Teaching Visual Arts; Youth and Adult Education; Experience Report